2016
DOI: 10.1111/modl.12349
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Intercultural Competence and Social Contact on Speech Act Production in a Chinese Study Abroad Context

Abstract: This study investigated the effects of intercultural competence and amount of social contact in the development of pragmatic knowledge. All these variables were time-varying variables and measured twice over a 3-month study abroad. Participants were 109 American college students studying Chinese in a semester study-abroad program in Beijing. Using Kelley & Meyers's (1995) instrument, intercultural competence-defined as one's potential to succeed in intercultural adjustment-was measured by 4 factors: emotional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
42
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 77 publications
(66 citation statements)
references
References 39 publications
(69 reference statements)
5
42
0
Order By: Relevance
“…The results suggest that actual ACCESS to learning opportunities (indicated by intensity of interaction), rather than mere AVAILABILITY of such opportunities (indicated by LoR), is a meaningful predictor of pragmatic competence. This finding adds to the limited empirical evidence showing a positive impact of interaction amount on pragmatic development (e.g., Matsumura 2003;Taguchi 2008;Taguchi et al 2013;Taguchi et al 2016), and reinforces Kasper & Rose's (2002) conclusion that LoR is not a reliable predictor of pragmatic competence.…”
Section: Approaches To Replication Of Studysupporting
confidence: 82%
See 2 more Smart Citations
“…The results suggest that actual ACCESS to learning opportunities (indicated by intensity of interaction), rather than mere AVAILABILITY of such opportunities (indicated by LoR), is a meaningful predictor of pragmatic competence. This finding adds to the limited empirical evidence showing a positive impact of interaction amount on pragmatic development (e.g., Matsumura 2003;Taguchi 2008;Taguchi et al 2013;Taguchi et al 2016), and reinforces Kasper & Rose's (2002) conclusion that LoR is not a reliable predictor of pragmatic competence.…”
Section: Approaches To Replication Of Studysupporting
confidence: 82%
“…3.1. Study 1: Taguchi, Xiao & Li (2016) This study, published in The Modern Language Journal, investigated the effects of a contextual factor (i.e., language contact) and an individual factor (i.e., intercultural competence) on the development of speech act production in L2 Chinese in a study abroad program. A line of studies revealed that exposure while abroad, assessed quantitatively via perceived amount of language contact or frequency of participation in social activities, was related to pragmatic gains (e.g., Matsumura 2003;Taguchi 2008;Bardovi-Harlig & Bastos, 2011;Taguchi, Li & Xiao, 2013).…”
Section: The Original Studies and Suggested Approaches To Replicationmentioning
confidence: 99%
See 1 more Smart Citation
“…A longer stay abroad was linked to a stronger reduction in anxiety levels in English. The lower anxiety levels after students returned home might be attributed to their improvement in language skills, for instance oral or auditory ability (Allen & Herron, 2003;Serrano, Llanes, & Tragant, 2016), pragmatic comprehension (Taguchi, 2011;Taguchi, Xiao, & Li, 2016), and intercultural adaptability and sensitivity (Williams, 2005). Overall, overseas experiences not only benefit the development of linguistic attributes and intercultural communication competence, but also enhance the students' psychological well-being.…”
Section: Introductionmentioning
confidence: 99%
“…This also applies to study abroad in China. Even though recent years have seen a surge of interest in research in this area (e.g., Diao, 2014; Du, 2013, 2015; Duff et al, 2013; He & Qin, 2017; Lee, Wu, Di, & Kinginger, 2017; Taguchi, Xiao, & Li, 2016), few studies have addressed the experience of ethnic minority American college students in the study abroad in China context, likely because of the low numbers of ethnic minority students who study in China. The current article is a case study of the only two African Americans and three Chinese Americans who participated in my research in 2013–2014, described in the “Methods” section of this article.…”
Section: Introductionmentioning
confidence: 99%